КӘСІПОРЫНДА МАКАРОН ӨНІМДЕРІНІҢ САПАСЫН ЖӘНЕ ҚАУІПСІЗДІГІН АНЫҚТАУ (Алматы технологиялық университетінің хабаршысы, 2021)
This article reflects the tendency of a total decrease in the quality of pasta, identified the causes of this problem and suggested ways to resolve it. Presented are the results of our own research, which allows us to judge that the decline in the quality of pasta is due to the transformation of state institutions in the sphere of technical regulation. The result of the study is to determine the benchmarks for the institutionalization of pasta.